Mobile multimedia communications concepts, applications, and challenges - Dooley, Laurence S., 1959-; Karmakar, Gour, 1970-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2008)
With rapid growth of the Internet, the applications of multimedia are burgeoning in every aspect of human life including communication networks and wireless and mobile communications. This book captures defining research on all aspects and implications of the accelerated progress of mobile multimedia technologies. Covered topics include fundamental network infrastructures, modern communication features such as wireless and mobile multimedia protocols, personal communication systems, mobility and resource management, and security and privacy issues. The book will meet the needs of researchers in a variety of related fields.
Introduction to Mobile Multimedia Communications / Gour Karmakar, Laurence Dooley, Michael Mathew -- Multimedia over Wireless Mobile Data Networks / Surendra Sivagurunathan, Mohammed Atiquzzaman -- Quality of Service Issues in Mobile Multimedia Transmission / Nalin Sharda -- On a Personalized System for Device Independent and Position Aware Communication / Odej Kao, Stefan Lietsch -- Mobile Multimedia for Speech and Language Therapy / Nina Reeves ... [et al.] -- A Proposed Framework for Mobile Services Adoption / Indrit Troshani, Sally Rao Hill -- Video Coding for Mobile Communications / Ferdous Sohel, Gour Karmakar, Laurence Dooley -- OFDM Transmission Technique / Hermann Rohling -- Routing Protocols for Ad-Hoc Networks / Muhammad Islam, Ronald Pose, Carlo Kopp -- Basics of Ubiquitous Networking / Kevin Park, Jairo Gutierrez -- Wireless Security and Privacy Issues / Joarder Kamruzzaman -- Security of Mobile Devices for Multimedia Applications / Goran Pulkkis ... [et al.] -- Security in Ad-Hoc Networks / Muhammad Islam, Ronald Pose, Carlo Kopp.
"Premier reference source".
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on July 7, 2010).
Keywords: Mobile communication systems; Multimedia communications; Ad-Hoc Networks; Mobile Multimedia Communications; Mobile Multimedia Transmission; Mobile Services Adoption; OFDM Transmission Technique; Pervasive Computing Applications; Position Aware Communication; Quality of Service Issues; Routing Protocols; Security in Ad-Hoc Networks; Security of Mobile Devices; Speech and Language Therapy; Ubiquitous Networking; Video Coding; Wireless Networks; Wireless Security and Privacy Issues; Wireless Sensor Networks; Electronic books